2017
DOI: 10.26522/brocked.v26i2.606
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Stress and Social Support Usage

Abstract: In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 30 publications
0
24
0
2
Order By: Relevance
“…This is reliable for the teaching function in Chile, with a Cronbach’s Alpha 0.941 and a Cronbach’s Alpha based on standardized items of 0.946 [ 31 ]. For the empirical analysis of the data, the principal component analysis (PCA) was used, a type of multivariate statistical analysis previously used in teaching-stress research [ 65 , 66 , 67 , 68 , 69 ]. Along with this process, the consistency of dimensions was analyzed using Cronbach’s Alpha, as presented in previous research [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is reliable for the teaching function in Chile, with a Cronbach’s Alpha 0.941 and a Cronbach’s Alpha based on standardized items of 0.946 [ 31 ]. For the empirical analysis of the data, the principal component analysis (PCA) was used, a type of multivariate statistical analysis previously used in teaching-stress research [ 65 , 66 , 67 , 68 , 69 ]. Along with this process, the consistency of dimensions was analyzed using Cronbach’s Alpha, as presented in previous research [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Experiencing stress, women more often than men seek social support [ 37 , 40 ]. Lack of social support, or insufficient social support, is positively related with emotional exhaustion [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of social support, or insufficient social support, is positively related with emotional exhaustion [ 41 ]. However, it has been indicated that too frequent talk about stress may have negative consequences in the form of the decrease of professional commitment and the sense of career [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, teachers' emotions are associated with teacher quality and relationship with students (for review of studies, see Frenzel et al, 2016): positive emotions are related to effective teaching (Frenzel et al, 2016;Makhwathana et al, 2017) and negative emotions frequently result in loss of control and negative behavior (Makhwathana et al, 2017). Teacher's performance may suffer owing to high levels of stress and this may impact on student learning (during distance education, too; Ferguson et al, 2017), and school reform (in our research study the term reform is associated with transformation of education due to the coronavirus pandemic) revealed potentially high levels of emotional stress triggered by externally mandated performance criteria (Yoo & Carter, 2017). Emotion and emotional distress, therefore, cannot be considered separate from the learning environment.…”
Section: Research Focusmentioning
confidence: 99%